Electronic Letter Box - Ahmad, Muhammad Firdaus; Suhaimi, Muhammad Fakharuddin (2016)
The function of letter box is a receptacle for receiving incoming mail at a private residence or business. There are many names of letter box such as letterbox, letter plate, letter hole, deed, mail slot and so on. Electronic Letter Box as a final year project. Choose this project because the electronic letter box have many advantages than disadvantages. The are many types of Electronic Letter Box especially function of the sensor. Sensor have many types such as sensor of sound, light, heat and so on. Next, all of project must have an objective and its purpose. The project that create is to help people especially to those who always using a letter to communicate or sent the information to others. This project will make people to know whether their letter had been reach or not. A letter doesn’t have any time period to reach at home. It will make people be waiting for a letter to reach at home. When the letter is already in the letter box, it will detected how many letter in the box and will produce light to inform that the letter has already reach at home. This project also will giving signal using buzzer. After that, the user will be informed that the letter had been reach at home. It will make user be easily to know the letter had been reach at home without need to be waiting for a long time. Besides that, the result of this project have been obtained through a data analysis, discussions, and hardware implementation result. There are few method to gain these result which are simulation method, measuring a reading of voltage and current using multimeter, and the mathematical equation to get the percentage error between the simulation result and actual result.